Advances in cardiology: from prevention to treatment - de Lacerda, Dhiego Alves; Lima, Larissa Luana Lopes; Honorato, Pedro Fechine; Vale, Renata Braga; das Neves, Diego Formiga; de Sá Filho, Claudenor Pinho; de Moura, Thiago Quirino; Figueiredo, Vinícius Costa; de Oliveira, Anaylle Vieira Lacerda; Isidório, Ubiraídys de Andrade (Revista Sistemática, 2024)
Cardiology is an ever-evolving medical field with significant advances in the diagnosis, prevention, and treatment of cardiovascular disease. This article reviews the latest developments in cardiology, from primary and secondary prevention strategies to innovative therapies for common heart conditions.